2015
DOI: 10.1007/s12079-015-0312-8
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of the involvement of the Wnt signaling pathway in Dupuytren’s disease

Abstract: Genetic background plays an important role in the development of Dupuytren’s disease. A genome-wide association study (GWAS) showed that nine loci are associated with the disease, six of which contain genes that are involved in Wnt signaling (WNT2, WNT4, WNT7B, RSPO2, SFRP4, SULF1). To obtain insight in the role of these genes, we performed expression studies on affected and unaffected patient’s tissues. Surgically obtained nodules and cords from eight Dupuytren’s patients were compared to patient-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…1 A-C). The results presented are in accordance with previous studies which showed increased COL1A1 mRNA in Dupuytren's tissue compared to unaffected transverse ligament of the palmar aponeurosis (Ten Dam et al, 2016) and increased COL1A1…”
Section: Discussionsupporting
confidence: 93%
“…1 A-C). The results presented are in accordance with previous studies which showed increased COL1A1 mRNA in Dupuytren's tissue compared to unaffected transverse ligament of the palmar aponeurosis (Ten Dam et al, 2016) and increased COL1A1…”
Section: Discussionsupporting
confidence: 93%
“…In other organs, downregulation of SFPR4 has been shown to promote myofibroblast activation during fibrosis 18, 19 . These results provide an elegant link between a genetic predisposition to fibrosis in DD and activation of Wnt signalling mediated through SFPR4 13, 16, 17 . Our understanding of the precise role of the genome in the pathogenesis of DD remains incomplete, but it appears that Wnt signalling may be crucial.…”
Section: Emerging Concepts In the Pathogenesis Of Dupuytren’s Diseasementioning
confidence: 77%
“…Wnt signalling has been associated with many other fibrotic diseases 14 but this was the first study highlighting this pathway as a potential key pathogenic driver in DD. Since then a number of studies have reported activation of Wnt signalling in DD 15 , including increased expression of the Wnt signalling protein Wnt7b in nodules 16 .…”
Section: Emerging Concepts In the Pathogenesis Of Dupuytren’s Diseasementioning
confidence: 99%
“…In Dupuytren's contracture, this pathway becomes overstimulated leading to fibrosis that invades the dermis resulting in contractures (Evert-Jan, van Beuge, Bank, & Werker, 2016). It is speculated that this process may be T-cell mediated involving the presence of CD3 lymphocytes (Evert-Jan et al, 2016). It is unclear as to whether one single gene is responsible for the development of Dupuytren's contracture or whether the etiology of the disease may be from environmental and/or occupational exposures, especially vibratory exposure, as well (Larsen et al, 2015).…”
Section: Dupuytren's Contracturementioning
confidence: 99%
“…The Wnt-signaling pathway regulates fibroblast proliferation (Dolmans et al, 2011). In Dupuytren’s contracture, this pathway becomes overstimulated leading to fibrosis that invades the dermis resulting in contractures (Evert-Jan, van Beuge, Bank, & Werker, 2016). It is speculated that this process may be T-cell mediated involving the presence of CD3 lymphocytes (Evert-Jan et al, 2016).…”
Section: Dupuytren’s Contracturementioning
confidence: 99%